Penggunaan Spinal Cord Independence Measure III sebagai Alat Ukur Kemampuan Fungsional Pasien Spinal Cord Injury di Indonesia - Sri Hartati Pratiwi; Debie Dahlia; Liya Arista (Journal of Telenursing (JOTING), 2023)
This study aims to determine the use of the Spinal Cord Independence Measure (SCIM) III as a functional measurement tool for spinal cord injury patients in Indonesia. The method used was cross-sectional as a pilot project. The population of this study were trauma and non-traumatic spinal cord injury patients. The results of this study indicate that SCIM III can assess the patient's functional status in self-care, bladder management, bowel management, and mobilization. In conclusion, SCIM III is an objective and reliable questionnaire that can be used as a tool to measure the functional ability of SCI patients. In addition, SCIM can be used to determine interventions that are appropriate to the patient's condition so that the outcome of the rehabilitation phase of care to make the patient independent can be achieved optimally. Keywords: Tool, Functional, Spinal Cord Independence Measure